Horn of Africa Emerging as a strategic pivot of the Indian Ocean Region: need for repackaging SAGAR 2.0. Issue 2 (4th May 2021) - Banerjee, Somen
ABSTRACT: Since the dawn of the twenty-first century, the Horn of Africa has undergone significant change. Presence of extra-regional powers has transformed the region into a strategic pivot of the Indian Ocean. But fractured societies of the region are in acute need of sustainable peace. Curiously, India's engagements with the Horn have been confined to peacekeeping operations and anti-piracy patrols. As a member of the United Nations Security Council in 2021 and 2022, India could do more. Against this backdrop, this article examines the salience of the Horn of Africa as a strategic pivot. It assesses the challenges and opportunities for engaging a region that is steeped in geopolitics but yearns for sustainable peace. It seeks to develop a framework for India's engagement in the Horn of Africa by evaluating the complementarities between the United Nations agenda of sustaining-peace and India's vision of Security and Growth for All in the Region.